2014
DOI: 10.1128/jcm.02178-14
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Tube Multiple-Locus Variable-Number Tandem-Repeat Analysis of Mycoplasma pneumoniae Clinical Specimens by Use of Multiplex PCR-Capillary Electrophoresis

Abstract: In this study, we developed a single-tube multiple-locus variable-number tandem-repeat (VNTR) analysis (MLVA) assay to type Mycoplasma pneumoniae directly from respiratory samples collected from children with respiratory infections. The multiplex PCR included four fluorescently primed VNTRs (Mpn13, Mpn14, Mpn15, and Mpn16) and was carried out in a single tube. A total of 137 M. pneumoniae-positive specimens, collected in 2013 from Beijing, China, were divided among four types (M4-5-7-2, M4-5-6-2, M3-5-6-2, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…In the United States, 13 (68.4%) of 19 MRMP isolates identified during CDCassisted investigations across the country between 2006 and 2013 belonged to MLVA type 4-5-7-2 (15). In China, this MLVA type accounted for Ͼ90% of the MRMP isolates identified in Beijing from 2010 to 2013 (12,22,24). Of the 21 distinct types that can be distinguished by the amended four-locus MLVA scheme (5, 6, 9-15, 22, 24-26) (see Table S1 in the supplemental material), MRMP has been detected in 12 types.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the United States, 13 (68.4%) of 19 MRMP isolates identified during CDCassisted investigations across the country between 2006 and 2013 belonged to MLVA type 4-5-7-2 (15). In China, this MLVA type accounted for Ͼ90% of the MRMP isolates identified in Beijing from 2010 to 2013 (12,22,24). Of the 21 distinct types that can be distinguished by the amended four-locus MLVA scheme (5, 6, 9-15, 22, 24-26) (see Table S1 in the supplemental material), MRMP has been detected in 12 types.…”
Section: Discussionmentioning
confidence: 99%
“…The MLVA type was designated by the numeric combination of the number of tandem repeats at four loci (Mpn13 to -16), as suggested previously (13,15). The number of repeats was rounded up to an integer value (9,12). The number of repeats in each locus (1 to 2 specimens for each product size) was confirmed by Sanger sequencing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the first report of its use in M. pneumoniae in 2009 [15], many studies over the world have consistently shown that MLVA typing is clearly more powerful than the standard P1 typing system in differentiating clinical strains [25,[32][33][46][47][48], and meanwhile there have been rising concerns about its stability, discriminability and correlation to clinical and epidemiological parameters [25,[31][32][33]. These concerns motivated us to seek deeper understanding of We have demonstrated that intrastrain variation occurred in different degrees in all 13 VNTR loci surveyed except for 3 loci (Mpn15, Mpn16 and Mpn103) (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, P1 restriction fragment length polymorphisms (RFLP) and multiple-locus variable-number tandem repeat (VNTR) analysis (MLVA) are the most widely used methods for strain typing for this pathogen (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). We improved the MLVA method by amplifying four VNTRs (without Mpn1) in one tube for epidemic and outbreak analyses (11).…”
mentioning
confidence: 99%